Graphene Quantum Dots from Agricultural Wastes: Green Synthesis and Advanced Applications for Energy Storage - Pierfrancesco Atanasio; Rubia Y. S. Zampiva; Luca Buccini; Corrado Di Conzo; Anacleto Proietti; Francesco Mura; Annalisa Aurora; Andrea G. Marrani; Daniele Passeri; Marco Rossi; Mauro Pasquali; Francesca A. Scaramuzzo (Molecules)
Carbon nanostructures are highly promising materials for applications in a variety of different fields. Besides their interesting performances, the possibility to synthesize them from biowaste makes them an eco-friendly resource widely exploitable within a circular economy context. The present work deals with the green, one-pot synthesis of graphene quantum dots (GQDs) from carbon aerogels (CAs) derived from rice husk (RH). After having obtained CAs upon purification of RH, followed by gelification and carbonization of the resulting cellulose, the one-pot solventless production of GQDs was obtained by ball milling. This method determined the formation of crystalline nanostructures with a diameter of around 20 nm, which were analyzed via scanning electron microscopy, transmission electron microscopy, atomic force microscopy, X-ray diffraction, and Raman spectroscopy to obtain a full morphological and structural characterization. GQDs were used as electrode materials for supercapacitors and Li-ion batteries, showing the ability to both accumulate charges over the surface and intercalate lithium-ions. The reported results are a proof of principle of the possibility of exploiting GQDs as support material for the development of advanced systems for energy storage.